Fotografía en América Latina : imágenes e identidades a través del tiempo y el espacio - Cánepa Koch, Gisela, 1964-; Kummels, Ingrid, (Arte y sociedad (Lima, Peru) ;, 2020)
Historical photographs taken in Latin America have shown their value as crucial sites for the politics of memory, ethnographic imagination and the negotiation of identity. This volume opens a set of questions related to the contemporary agency of this type of images, as well as their current appropriation through new technologies.